"Mask up to keep it up": Preliminary evidence of the association between erectile dysfunction and COVID‐19. (30th March 2021) - Sansone, Andrea; Mollaioli, Daniele; Ciocca, Giacomo; Colonnello, Elena; Limoncin, Erika; Balercia, Giancarlo; Jannini, Emmanuele A.
Abstract: Background: Erectile dysfunction (ED), as the hallmark of endothelial dysfunction, could be a short‐ or long‐term complication of COVID‐19. Additionally, being ED a clinical marker and predictor of non‐communicable chronic diseases, particularly cardiovascular, subjects with ED could potentially have a higher risk of contracting COVID‐19. Objectives: To investigate the prevalence of ED among subjects with a reported diagnosis of COVID‐19 and to measure the association of COVID‐19 and ED. Materials and methods: We reviewed data from the Sex@COVID online survey (performed between April 7 and May 4, 2020, in Italy) to retrieve a sample of Italian male sexually active subjects with reported SARS‐CoV‐2 infection. A matching sample of COVID‐19‐negative male sexually active subjects was also retrieved using propensity score matching in a 3:1 ratio. The survey used different standardized psychometric tools to measure effects of lockdown and social distancing on the intrapsychic, relational, and sexual health of Italian subjects. Results: One hundred subjects were included in the analysis (25 COVID‐positive; 75 COVID‐negative). The prevalence of ED, measured with the Sexual Health Inventory for Men, was significantly higher in the COVID+ group (28% vs. 9.33%; p = 0.027). Logistic regression models confirmed a significant effect of COVID‐19 on the development of ED, independently of other variables affecting erectile function, such as psychological status, age, and BMI [OR 5.66, 95% CI: 1.50–24.01]. Likewise, subjects with ED were more likely to have COVID‐19, once corrected for age and BMI [OR 5.27, 95% CI: 1.49–20.09]. Discussion and conclusion: On top of well‐described pathophysiological mechanisms, there is preliminary evidence in a real‐life population of ED as a risk factor of developing COVID‐19 and possibly occurring as a consequence of COVID‐19. Universal vaccination against the COVID‐19 and the personal protective equipment could possibly have the added benefit of preventing sexual dysfunctions.